Digital Citizenship: Importance of Education and Training for Medical Teachers and Students (Bangladesh Journal of Medical Biochemistry, 2025)
The concept of digital citizenship relates to the responsible, ethical and safe use of digital technologies by all of us as members of society and citizens of the global community. In recent times, digital technologies have had an enormous impact on the students’ learning in medical education. Digital literacy is important now-a-days in current medical education whether being a medical teacher or a student. With the rise of technology users, this shows the importance of being knowledgeable about fraud, misinformation, and disinformation. We sometimes fail to choose credible and valid sources across different online media. We also spread news and information unknowingly or ignoring their hidden agenda. Moreover, we share some interesting medical cases or incidents violating our country’s legislation or without proper consent or maintaining privacy or denouncing institutional policy. Many of us have already experienced internet fraud or cyberbullying. Hence, digital citizenship education is necessary to protect ourselves from being vulnerable to those above-mentioned issues. Digital citizenship education can be implemented face-to-face, or online or in hybrid format, which provides medical educators and students with the skills needed to make use of current technology and social media tools to support teaching and learning as well as their personal presence in the digital world. We are convinced that our medical teachers and students need to use new technologies in an appropriate manner to create better learning environments, materials, and networks. Digital citizenship education can be achieved by coordination of BM&DC, medical colleges and higher training institutions implementing programs which will encourage faculties and students to expand proper knowledge, skill and attitude towards digital citizenship.Bangladesh J Med Biochem 2020; 13(2): 63-70